Overexpression of 1-Aminocyclopropane-1-Carboxylic Acid Deaminase (acdS) Gene in Petunia hybrida Improves Tolerance to Abiotic Stresses - Naing, Aung Htay; Jeong, Hui Yeong; Jung, Sung Keun; Kim, Chang Kil (Frontiers in Plant Science, 2021)
Abiotic stress induced the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) in plants, which consequently enhanced ethylene production and inhibited plant growth. The bacterial ACC deaminase enzyme encoded by the acdS gene reduces stress-induced ethylene production and improves plant growth against stress. In this study, overexpression of acdS in Petunia hybrida (‘Mirage Rose’) significantly reduced ethylene biosynthesis gene ACC oxidase 1 (ACO1) expression and ethylene production relative to wild type (WT) under various abiotic stresses (cold, drought, and salt). The higher reduction of stress-induced ethylene in the transgenic plants, which was due to overexpression of acdS, led to a greater tolerance to the stresses compared to that in the WT plants. The greater stress tolerances were proven by exhibiting better plant growth and physiological performance that were linked to stress tolerance. Moreover, the expression analysis of the genes involved in stress tolerance also supported the transgenics’ greater tolerance to WT. These results suggest the possibility of acdS being overexpressed in ornamental plants, particularly in bedding plants normally growing outside the environment, to overcome the deleterious effect of ethylene on plant growth under different abiotic stresses. The development of stress-tolerant plants will be helpful for the advancement of the floricultural industry.